Sektorowa struktura pracujących w UE jako podstawa klasyfikacji przestrzeni regionalnej - Strahl, Danuta; Markowska, Małgorzata (Sector oriented structure of employees in EU as the basis for regional space classification, 2006)
The article presents an attempt to identify structural picture of European regional space. Regions of European Union countries at NUTS-2 level constitute the subject of the study. Spatial structure was identified by means of variables which describe employment in four economy sectors. The identification of European regional structure in EU was performed by means of hierarchical classification method, which facilitated introducing order into the European regional space with reference to the structure of employees in economic sectors of economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 308-316